Globalization and Public Policy: A European Perspective - Audretsch, D (Springer, 2015)
This volume of selected articles was released in light of the new economic, social and environmental challenges Europe and the United States have been faced with following the end of the Cold War and in the evolving era of globalization. National security, immigration, and the provision of health and other key social services call for a radically different outlook in terms of policy discussions. The contributors of this book focus on seven key policy issues and challenges that currently affect the United States and Europe: income distribution, the gender pay gap, crime and security, unemployment, health care, the demographic question, and environmental regulation. The purpose of this volume is to analyze how public policy within the European context is responding to the challenges posed by this new global era.